How mobile phone addiction leads to college students’ learning burnout: the role of depression as a mediator and fear of missing out as a moderator - Song, Tianxiang; Zhu, Hongze; Yang, Kaixu; Chang, Wenhao; Ni, Jianchao (Frontiers in Psychiatry, 2025)
BackgroundWith the widespread use of smartphones, mobile phone addiction is becoming increasingly common among college students, which has a negative impact on their learning. This study aims to explore how mobile phone addiction leads to college students’ learning burnout, with a focus on the mediating role of depression and the moderating role of FOMO (Fear of Missing Out).MethodsConvenient sampling was used to collect 1862 valid questionnaires from over 10 universities in China. A moderated mediation model was constructed to analyze the relationship and mechanism among mobile phone addiction, learning burnout, depression and FOMO through structural equation modeling.Results(1) Mobile phone addiction has a significant positive impact on college students’ learning burnout (β=0.4767, p < 0.001); (2) Depression plays a partial mediating role between mobile phone addiction and learning burnout (95% CI= [0.0706,0.1145]), with the mediating effect accounting for 19.34% of the total effect; (3) FOMO moderates the relationship between depression and learning burnout. Specifically, depression has a stronger impact on learning burnout among college students with low FOMO.ConclusionThis study reveals the mechanism of mobile phone addiction on college students’ learning burnout, and confirms the mediating role of depression and the moderating role of FOMO. By integrating Self-Determination Theory, we further explain the specific mechanisms of FOMO’s moderating role. This offers a which provides a new perspective for understanding the impact of mobile phone addiction on college students’ learning burnout. It also provides a theoretical basis for colleges and universities to carry out mental health education and intervention.